PERFORMANCE EVALUATION OF PLASTIC GRANULES AND QUARRY DUST AS FINE AGGREGATE IN M40 GRADE CONCRETE - Nisha, Mrs.I.Rahmath; Ganga, Mrs.T. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
In this context an experimentalstudy is done based on Quarry Dust Wastes(QDW) and polypropylene plastic granules(PPG) for replacement of fine aggregate inconcrete. The strength properties of M40grade concrete is studied with differentproportions of plastic granules and quarrydust along with addition of 1% superplasticizer. The various proportions of plasticand quarry dust used are 25% and 30%replacement by volume of river sand in theconcrete. Strength tests are carried out withdifferent proportions of replacements of riversand with QDW and PPG. Cube specimens,cylinder specimens and prism specimens of 9numbers each were cast for differentproportions of M40 concrete , cured andtested for 7 ,14 and 28 days. Compression,split tensile and flexural strength tests weredone and the results are compared with100% river sand concrete specimens.Keyword - river sand, polypropylene plasticgranules, quarry dust, industrial wastes,super plasticizer.